PAKISTAN’S MARCH TOWARDS UNIVERSAL HEALTH COVERAGE - Khan, Sheraz Ahmad (Journal of Ayub Medical College Abbottabad, 2017)
Millions across the globe lack access to needed health services, amidst poverty. In countries with higher out of pocket (OOP) expenditure on health, medical bills impoverish masses. Therefore, World Health Organization (WHO) is advocating to bring OOP expenditure to zero by 2030 and ensure Universal Health Coverage (UHC). WHO defines UHC as access to key promotive, preventive, curative and rehabilitative health interventions for all at an affordable cost, thereby achieving equity in access.1,2 To materialize UHC, central government in Pakistan and provincial government in Khyber Pakhtunkhwa have started two social health protection schemes. Together, these schemes would cover approximately 49 million people for all secondary healthcare conditions requiring admission. Limited inpatient tertiary care is also covered. Beneficiaries are those living below the national poverty line. Respective government(s) pay premium for the poor households to an insurance firm, which in turn procures healthcare services for the covered population through a network of public and private hospitals. These projects are applying cash-free mechanism at point of service. Financial protection worth several hundred thousand of rupees is conferred upon these households and cost billions of rupees to respective government(s) in premium, annually.3,4 These schemes are need of the day and a positive omen of strengthening democracy in Pakistan. Both the ruling party in central government and that in KP had pledged health insurance in their election manifestos, the same promises are now honoured.5,6 This shift in our public health spending was inevitable as out of pocket health expenditure had touched 70% of our net expenditure on health, despite the fact that 29% of the population lives below the national poverty line.7,8 Though the basic benefit of these schemes in improving access to needed health services, they also have significant potential transform our entire healthcare system for the better. In 2010, a multilateral conference took place in Dubai, to cater support for transitioning democracy in Pakistan. This conference inter-alia discussed healthcare reforms, whereby public-private-partnership (PPP) was stressed upon. Many countries have reported benefits from PPP, which brings efficiency of private sector to public and vast infrastructure of public sector to the private sector.9 These social health protection schemes have effectively brought PPP into force, wherein scores of private hospitals are rendering services through public financing. It is a good start indeed, however, in countries where roles are ill-defined and rules are lax, the private sector tend to assert its political clout, inflate costs and incentivize care of the middle and upper class more than the poor. These things if happen in our social health protection schemes, would be detrimental to public sector and public health in long run.10 Interestingly, we are getting some significantly positive by product(s) with these schemes. Vital registrations including birth and death certificates have been historically low in our poorest population. Now that each birth registered under the scheme brings a financial incentive for the household, and as every birth happening during the policy period enrols the baby without any co-payment(s), we are observing a rise in birth registration. Similarly, every death occurring in hospital during the policy period has a disbursement plan of Rs. 10,000/- for funeral, death registrations/ documentation will also improve. Moreover, to avail paediatric services under the scheme, all children below 18 years of age have to bear a valid Form-B issued by the National Database and Record Authority (NADRA) of Pakistan, which will bring all children under 18 on record of the national database. Most interestingly, marriage registration with the NADRA database will also surge. Data used for these schemes come from Benazir Income Support Program (BISP). BISP data had declared women as household heads in majority cases. Now that these insurance schemes proactively enrol household head’s spouse in beneficiaries’ net, the insurance firm at some point will be pressing for production of marriage registration(s). Hence, the outlook of these vital data registration(s) are quite positive. These schemes will also improve the quality of our healthcare services indiscriminately. During our in-house discussion(s), I proposed to declare improving the quality of healthcare services as an objective of our project. After some reluctance to the idea (as quality assurance is primary job of other government functionaries and fear of backfire in public sector), my colleagues agreed to this point. The underlying rationale is simple, as this scheme has billions of rupees at offer for the public-private mix, it has to respond to the financial incentive. A strict criterion to retain hospitals on panel shall indigenously set quality benchmarks and again, accreditation system will ensue as an outcome of these schemes. It is pertinent to mention that, with most of our national out of pocket expenditure on healthcare is incurred in private sector.7 Jeffary D.Sacchs, leading development economist pinned some pertinent issues of public sector providers. He pointed towards monopolized and unionist architecture of public sector as well as its technological laggardness, poor quality and corruption as causes of low client satisfaction. Now that, the private sector will shoulder public sector’s burden, it will have a transition time to improve its quality. Also, with the strong backbone of Management Information Systems (MIS) both at the Prime Minister and Khyber Pakhtunkhwa scheme, the poor performers among government sector can’t hide, which definitely will bring it an ire from higher authorities. Just few months into the scheme, we are observing certain patterns in our data and we are sure that poor counts at any hospital will have to be accounted for. We also need to contextually understand these schemes. Healthcare reforms work in tandem and considering things in isolation can demean singular initiatives. The outburst of healthcare workers in KP with introduction of Medical Teaching Institution (MTI) reforms, which devolved the financial powers from secretariat to the individual institutions was villainized. This law however, if had been repealed would have put these seven-teaching institutions at odd to the health insurance model. It is the financial autonomy that these teaching institutions can now enter into service agreement(s) with the insurance firm, earn revenue from services to the covered households and spend the revenue made on hospitals’ upkeep, quality enhancement and workers remunerations. Moreover, the institutional private practice which hitherto was in limbo, and which even failed when attempted by powerful military regime previously, seems more plausible now. Holders of these insurance policies can cosily get treated at standard private hospitals as well as the reputed public-sector teaching hospitals under the institutional private practice window, which ensures premium services! With positive points enumerated above, caution about the following points is necessary: To achieve UHC with these schemes, they have to further broaden their clientele, increase disease coverage and bring institutional reforms. However, these changes will be sternly faced with political, legal and financial constraints. These schemes in current form are not viable financially. There has to be a contributory arm and subsidy should be more focused. These schemes started in a legal void. Healthcare is not guaranteed in our constitution and an overarching legal framework to sustain these schemes is not in place. Constitutional reforms, statutory framework and political concurrence are pre-requisite for UHC.11 The downside of 18th constitutional amendment is a fractured healthcare system which hitherto has not been reconstituted by provinces. Delicate constitutional balance between the central government and federating units (provinces) is needed.12 To summarize, social health protection (insurance) schemes recently launched in Pakistan can potentially lead towards UHC. Prospects for these schemes to contribute towards SDGs are bright and will have far reaching impact on improving the quality of our healthcare system as well as improving our vital statistics’ registration. However, financial, political and legal restraints have to be considered en-route to Universal health coverage, which may need mid-policy reforms continually.